Program Pengendalian Filariasis di Kabupaten Donggala, Sulawesi Tengah - Made Agus Nurjana; Hayani Anastasia; Junus Widjaja; Yuyun Srikandi; Anis Nur Widayati; Murni Murni; Phetisya Pamela Frederika Sumolang; Ade Kurniawan; Mujiyanto Mujiyanto; Resmiwaty Resmiwaty (Balai Penelitian dan Pengembangan Kesehatan Donggala, Badan Penelitian dan Pengembangan Kesehatan, Kementerian Kesehatan RI, 2020)
Abstract Donggala district had successfully conducted Transmission Assesment Survey–1 despite two children found positive for Brugia malayi. This study aimed to determine the progress of the filariasis program in Donggala District, Central Sulawesi. It was conducted in Kabonga Kecil, Banawa Sub-District and Sabang, Dampelas Sub-District from February to November 2017. Data collection included finger blood surveys, detection of Brugia malayi DNA, mosquito surveys, and in-depth interviews. From 638 people tested for finger blood survey, none of them were positive for microfilaria. Twenty children were tested for Brugia malayi DNA and the results were negative. A total of 2.978 mosquitoes were caught from mosquito surveys which identified as Aedes, Anopheles, Armigeres, Culex, Mansonia, Aedomyia, Uranotaenia, and Coquillettidia. PCR examination results showed all mosquito negative for Brugia malayi. A comprehensive and integrated surveillance strategy with other programs that are cost-effective and sustainable must continue to be carried out therefore the elimination of filariasis in the Donggala district can be achieved. Abstrak Kabupaten Donggala lulus Transmission Assesment Survey-1 meskipun masih ditemukan dua anak positif antibodi Brugia malayi. Penelitian ini bertujuan untuk mengetahui capain program filariasis di Kabupaten Donggala, Provinsi Sulawesi Tengah. Dilaksanakan di Kelurahan Kabonga Kecil, Kecamatan Banawa dan Desa Sabang, Kecamatan Dampelas pada bulan Februari – November 2017. Kegiatan meliputi survei darah jari, deteksi DNA Brugia malayi, survei nyamuk dan wawancara mendalam. Sebanyak 638 masyarakat diperiksa darahnya hasilnya seluruhnya negatif microfilaria. Sebanyak 20 anak diambil sampel darah untuk diperiksa deteksi DNA Brugia malayi hasilnya negatif. Nyamuk tertangkap sebanyak 2.978 nyamuk dari genus Aedes, Anopheles, Armigeres, Culex, Mansonia, Aedomyia, Uranotaenia, dan Coquillettidia. Hasil pemeriksaan PCR menunjukkan seluruh nyamuk negatif Brugia malayi. Strategi surveilans yang comprehensif dan terintegrasi dengan program lain yang cost-effective dan berkesinambungan harus terus dilakukan agar eliminasi filariasis di kabupaten Donggala dapat tercapai.